Ekonomistický redukcionismus a humanistická perspektiva v současné sociologii náboženství = Economical reductionism and humanistic perspective in contemporary sociology of religions - Nešpor, Zdeněk R. (Religio, 2004)
In this article the author concerns with different theoretical and methodological approaches in the contemporary sociology of religions. He argues that after the fall of the secularization thesis in the 1980s, two different "new paradigms" have emerged. The first one he identifies as an economical approach of the rational (religious) choice theory, established by R. Stark and his colleagues, while the second one as a humanistic approach of P. L. Berger and other, usually European, widely oriented sociologists. The author argues that this differentiation is connected both with interdisciplinary domination of economic and economic - like thought in humanities and social sciences (conceptualizing religious markets etc.), and with multiplication of approaches in the contemporary economy and economic sociology. While the rational choice theorists have found the backgrounds of their theory in the neoclassical economics, the approach of the others can be connected with economic sociology and other critics of neoclassical paradigm. -- After brief description of both paradigmatic ways in the contemporary sociology of religions, the author turns to their comparison and critical evaluation. He deals mainly with the "window-signs" of the rational choice approach, like the explanations of differences between competitive religious markets and religious monopolies, overwhelming growth of the strict denominations, etc. Although he agrees with some of these explanations, he usually finds them too reducing, due to the fact they ignore historical and systematic divergences of religious markets. Also the rationality of religious behaviour itself seems to be more observers' wish or the self-fulfilling prophecy than real description of social and symbolic functioning of religion, while the approach puts almost no attention to privatized, "organization-less" forms of religious expression and/or its functional equivalents. Due to these interpretational lacks of the rational religious choice theory the author summarizes that the so-called humanistic approach to the study of religions seems to be more satisfied, especially with respect to the (re)building of Czech sociology of religions. The advantages of the economic-like approach, especially the theory's possibility of operationalizing and making the quantitative surveys, seems not worth enough for its application, neither for its wider social, politic and other use.